CALCULATION OF ECOSYSTEM VALUE INDEX FOR COASTAL WATERS OF CON CO ISLAND - Lan, Tran Dinh; Chien, Hoang Thi (Vietnam Journal of Marine Science and Technology, 2017)
Based on ecosystem values of coastal waters in Con Co island estimated in the national project coded KC09.08/11-15, indices of ecosystem values were developed and calculated with three components: direct use value index (Idev) of 40.2, indirect use value index (Iidev) of 55.2 and non-use value index (Inuv) of 100. An index of the total ecosystem economic value (Ieev) for the studied area was calculated at 65.1, equal to 370,350 million VND per year at present. At assessment scale of 100 points with one forth interval, economic values of coastal ecosystems of Con Co island are high